Pengaruh Strategic Leadership terhadap Competitive Advantage melalui Intellectual Capital sebagai Variabel Intervening terhadap perusahaan manufaktur - Tanoni, Novita Andriani (Business Accounting Review, 2016)
The purpose of this study was to examine to test the affect of strategic leadership on competitive advantage through intellectual capital as the intervening variable on manufacturing companies in Surabaya. Sample of this study was 30 manufacturing companies in Surabaya. Data were collected by distributing questionnaire to the companies. This study used path modeling analysis technique with PLS tools. The results showed that there were positive and significant affect of strategic leadership on competitive advantage, positive and significant affect of strategic leadership on intellectual capital, and also positive and significant affect of intellectual capital on competitive advantage on manufacturing companies in Surabaya.